Religie en representatie: De religieuze invloeden in het gevangenenverslag van Maria ter Meetelen (1731-1743) - te Kronnie, Judith (Skript Historisch Tijdschrift, 2025)
‘How wonderfully God preserves those who trust in him.’ This is how Maria ter Meetelen concludes her account of her imprisonment, based on her life as a slave in Morocco between 1731 and 1743. Mary published this account five years after her liberation under the name: ‘Miraculous and remarkable cases of a twelve-year-old slave, of a woman named Maria ter Meetelen, living in Medenblik’. The account has gained much notoriety among historians, mainly because of Mary’s assertive attitude, but Mary herself emphasizes the importance of religion during her imprisonment. However, religion often influences reporting, but this has been studied to a limited extent. That is why this article examines the influence of religion on Maria ter Meetelen’s account. For example, the account often refers to times when she prayed to God and contains phrases that closely resemble the biblical Christmas story or a hagiography.